The Effects of Field Massage Technique on Bilirubin Level and the Number of Defecations in Preterm Infants - Soheila Karbandi; Maryam Lotfi; Hasan Boskabadi; Habibollah Esmaily (Mashhad University of Medical Sciences, 2015)
Background: Hyperbilirubinemia is a common physiological problem in approximately 80% of preterm infants during the first week after birth. Increase in bowel movements reduces enterohepatic circulation and increases bilirubin excretion. Aim: This study aimed to evaluate the effects of Field massage technique on bilirubin level and the number of defecations in preterm infants Method: This clinical trial was performed on 80 preterm infants aged 30-36 weeks, who were hospitalized in neonatal intensive care units of Qaem, Imam Reza, and Ommolbanin hospitals of Mashhad, Iran, in 2011. The enrolled infants were randomized into intervention and control groups. The control group received the routine care, and the intervention group received a 15-minute massage twice a day (morning and evening), for five consecutive days. Field massage technique was applied by the researcher. The number of defecations and cutaneous bilirubin level were recorded on a daily basis until the sixth day after birth. Independent t-test and Mann-Whitney U test were performed to analyze the data, using SPSS version 14. Results: The mean age of the intervention and control groups was 17.2±4.5 and 17.1±4.5 hours, respectively. The mean level of cutaneous bilirubin in the intervention and control groups on the first and sixth days were not significantly different (10.7±1.5, 10.8±1.4, 13.4±2.0, and 13.4±2.6, respectively; the first day: P=0.67, the sixth day: P=0.98). The number of defecations on the fourth (P=0.01), fifth (P